Analysis of PAI Students' Readiness for the Integration of Artificial Intelligence in Learning at Ahmad Dahlan University - Saukina Putri; Arif Rahman (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The rapid advancement of the digital era has accelerated the integration of Artificial Intelligence (AI) into higher education, including the learning process in the Islamic Religious Education (PAI) Study Program at Universitas Ahmad Dahlan. AI offers significant opportunities to improve learning effectiveness, yet its successful implementation depends on students' readiness to use it responsibly and effectively. This study aims to analyze the readiness of PAI students for the integration of AI in learning by examining their understanding, perceptions, and ability to utilize AI as an academic support tool. An explanatory sequential approach was employed, with data collected through classroom observations, in-depth interviews with PAI students, and documentation of AI-assisted learning activities. The findings indicate that most PAI students have positive perceptions and are receptive to the use of AI, particularly for conducting literature searches, completing academic assignments, and enhancing conceptual understanding. However, their readiness has not yet reached an optimal level due to limited digital literacy, insufficient understanding of academic ethics, and concerns about excessive dependence on AI. The study concludes that PAI students are generally prepared to integrate AI into learning, provided that digital competencies, ethical awareness, and Islamic values are continuously strengthened to ensure the responsible and meaningful use of AI in Islamic education.